Vedic practice, ritual studies and Jaimini's Mīmāṃsāsūtras: dharma and the enjoined subject - Ngaihte, Samuel (Routledge Hindu studies series, 2020)
Conceptual framework -- Pursuit of dharma -- Authority of Veda -- Realization of dharma.